Optimisation of arsenic adsorption from water by carbon nanofibers grown on powdered activated carbon impregnated with nickel. - Al-Mamun, Abdullah; Al-Khatib, Ma An Fahmi Rashid; Abdul Kadir, Zahirah; Ahmed, Yehya M.; Mohammed, A. R. S.; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Ismail, Ahmad Faris; Idris, Azni (Asian Network for Scientific Information, 2009)
Contamination of water due to arsenic (As) is increasing in many parts of the world. The removal of As from aqueous solution by using impregnated carbon nanofibres (CNFs) as the adsorbent is reported in this paper. The effects of pH, CNFs dosage, contact time and initial concentration of arsenic were at room temperature (±25°C).